2015
DOI: 10.1136/bjophthalmol-2014-306545
|View full text |Cite
|
Sign up to set email alerts
|

Childhood intermittent exotropia from a different angle: does severity affect quality of life?

Abstract: It is difficult to predict child HRQOL based on clinical measurements. However, parent HRQOL tends to be worse with poorer control and larger angle of deviation. Perhaps HRQOL should be routinely assessed in clinic alongside clinical measurements in order to tailor management appropriately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 23 publications
2
12
1
Order By: Relevance
“…Our analysis showed that the angle of deviation had no effect on intelligence in exotropia children. This finding is in line with the previous observation that there is no correlation between deviation severity and psychological parameters in exotropia patients [38]. During the pathogenesis of exotropia, the stereoacuity, control, and angle of deviation are unstable, and exotropia children may exhibit any combination of stereoacuity, control, and angle of deviation [39].…”
Section: Discussionsupporting
confidence: 91%
“…Our analysis showed that the angle of deviation had no effect on intelligence in exotropia children. This finding is in line with the previous observation that there is no correlation between deviation severity and psychological parameters in exotropia patients [38]. During the pathogenesis of exotropia, the stereoacuity, control, and angle of deviation are unstable, and exotropia children may exhibit any combination of stereoacuity, control, and angle of deviation [39].…”
Section: Discussionsupporting
confidence: 91%
“…However, in that study a wide variety of strabismus types were included in their analysis. In the Wang et al's study, the deviation angle at distance and exotropia control at home were associated with the child's HRQOL [22] , while Lim et al believed that the child's HRQOL and clinical severity were not related [10]. Our current results were mixed, that is, the child's IXTQ was related to near stereoacuity, but not to the deviation angle, NSC and distant stereoacuity.…”
Section: Discussioncontrasting
confidence: 52%
“…In general, the more severe the IXT, the worse the HRQOL. However, Hatt and Lim [9,10] found that while parents' HRQOL was related to the children's IXT severity, no such relationship was present in the children. In this way, the clinical ndings of IXT in these children do not fully correspond with their mental health.…”
Section: Introductionmentioning
confidence: 96%
“…However, in that study, a wide variety of strabismus types were included in the analysis. In Wang et al’s study, the deviation angle at distance and exotropia control at home were associated with the child’s HRQOL [ 22 ], whereas Lim et al believed that the child’s HRQOL and clinical severity were not related [ 10 ]. Our current results were mixed; that is, the child’s IXTQ was related to near stereoacuity but not to the deviation angle, NSC or distant stereoacuity.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the more severe the IXT, the worse the HRQOL. However, Hatt and Lim [ 9 , 10 ] found that whereas parents’ HRQOL was related to children’s IXT severity, no such relationship was present in the children. In this way, the clinical findings of IXT in these children do not fully correspond with their mental health.…”
Section: Introductionmentioning
confidence: 99%